Avaliação dos resultados alcançados após implantação da manutenção produtiva total (TPM / MPT) em uma indústria de cerveja - Bazi, Frank de Lima (2014)
Due to the increasing competitiveness between organizations , the need arises to be analyzed production processes of enterprises for the reduction of waste generated during manufacturing . Often the need for changes or improvements in supply chain processes . Through these enhancements , companies may be meeting the needs of customers . This study aims to demonstrate the results of the implementation of total productive maintenance in a brewery, search promote the engagement of all the employes and envolve them making them believe that a tool implemented is to manage the processes and make them more efficient and effective thus it will certainly bring results. Thus, Total Productive Maintenance - TPM comes to revolutionize the system of manufacturing industries and the same time to bring industrial excellence. TPM has been adopted by many companies in Brazil, such as Yamaha, GM, Alcoa, Ford, Azalea, AmBev, Multibrás, Tilibra, Heineken etc.. The objective of the program is the involvement of people because without it the system is worth nothing. The basis of the program is the application of the existing methodology, step by step, for easy understanding and with a noticeable positive return. It consists of pillars that direct the work of the team sinto a more assertive approach by attacking the problems directly in their root cause. They represent efficiency, self-repair, planning, training and lifecycle. Some of the obtained results are: improvement of the percentage in come of the production lines; reduction of the electricity and thermal consumption; break downs reduction; revitalized work places they can provide welfare for the employees.